2014
DOI: 10.1002/asia.201402207
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Catecholates for Cellular Imaging and Photocytotoxicity in Red Light

Abstract: Iron(III) complexes [Fe(L)(L')(NO3)]--in which L is phenyl-N,N-bis[(pyridin-2-yl)methyl]methanamine (1), (anthracen-9-yl)-N,N-bis[(pyridin-2-yl)methyl]methanamine (2), (pyreny-1-yl)-N,N-bis[(pyridin-2-yl)methyl]methanamine (3-5), and L' is catecholate (1-3), 4-tert-butyl catecholate (4), and 4-(2-aminoethyl)-benzene-1,2-diolate (5)--were synthesized and their photocytotoxic properties examined. The five electron-paramagnetic complexes displayed a Fe(III)/Fe(II) redox couple near -0.4 V versus a saturated calom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…The catecholate complexes 1 – 3 exhibited an additional reversible response near E =0.5 V relative to the redox profile of the respective dichloro precursor complexes (Figure ). Therefore, this couple was assigned to the catecholate and semiquinone radical species; this is a well‐known characteristic of the catecholate complexes …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The catecholate complexes 1 – 3 exhibited an additional reversible response near E =0.5 V relative to the redox profile of the respective dichloro precursor complexes (Figure ). Therefore, this couple was assigned to the catecholate and semiquinone radical species; this is a well‐known characteristic of the catecholate complexes …”
Section: Resultsmentioning
confidence: 97%
“…Therefore, this couple was assigned to the catecholate and semiquinone radicals pecies; this is aw ell-known characteristic of the catecholate complexes. [37,38] The complexes werer eadily soluble in polar solvents like MeOH,M eCN, DMSO,a nd DMF.T he stability of the complexes was studied (25 mm in 1% DMSO/DPBS, pH 7.2) by monitoring the changes in the absorption spectra with time. It was observed that the complexes were stable in the dark for 48 h. There was no apparent change in their absorption spectra upon photoirradiation for 1h (l = 400-700nm, light dose = 10 Jcm À2 ), whichi ndicated their photostability ( Figure S17 in the SupportingI nformation).…”
Section: Synthesis and General Propertiesmentioning
confidence: 99%
“…Standard experimental procedures were adopted for plating the cells and processing them after treatment with the complexes (see Supporting Information). 38 ■ RESULTS AND DISCUSSION Synthesis and General Aspects. The tridentate Schiff base (H 2 L 1 ) of pyridoxal hydrochloride as yellow orange crystalline solid was prepared by reacting it with 2-aminophenol.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Iron is an essential element for the human body, and enzymes containing iron could catalyze organic oxidation reactions . Recently a class of iron(III) catecholates was reported that showed photocytotoxicity with the complexes primarily localizing in the nucleus or mitochondria of HeLa and HaCaT cells . Moreover, new NCN pincer iron(III) complexes have been reported as cytotoxic assays in human colon cancer (HCT‐15), lung cancer (SKLU), and gastric cancer (AGS, KATOIII) cells with IC 50 values more than cisplatin for all cell lines …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Recently a class of iron(III) catecholates was reported that showed photocytotoxicity with the complexes primarily localizing in the nucleus or mitochondria of HeLa and HaCaT cells. [20][21][22] Moreover, new NCN pincer iron(III) complexes have been reported as cytotoxic assays in human colon cancer (HCT-15), lung cancer (SKLU), and gastric cancer (AGS, KATOIII) cells with IC 50 values more than cisplatin for all cell lines. [23] Recently, ferrocenyl (Fc) groups linked to borondipyrromethenes (BODIPYs) via a spacer located at mesoposition have been published during recent years.…”
Section: Introductionmentioning
confidence: 99%